2010
DOI: 10.1177/1938640010375114
|View full text |Cite
|
Sign up to set email alerts
|

Split-Thickness Skin Grafts for Closure of Diabetic Foot and Ankle Wounds

Abstract: The aim of this study was to determine if split-thickness skin grafts could be successfully used for closure of foot and ankle wounds in diabetic patients. The authors retrospectively reviewed the charts of 100 consecutive patients who underwent a soft tissue surgical reconstruction with split-thickness skin grafts to their foot and/or ankle in our institution from 2005 to 2008. After application of inclusion criteria, 83 eligible charts remained. Of the 83 patients, 54 (65%) healed uneventfully, 23 (28%) requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
0
36
1
Order By: Relevance
“…One shortcoming of our study is that we did not quantitatively analyze preoperative glycemic control. However, Ramanujam et al did not find a statistically significant difference in preoperative hemoglobin A1C levels and healing time, despite high average preoperative hemoglobin A1C values in their patients (10). Conversely, a study by Marston found a direct correlation between hyperglycemia and wound healing.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…One shortcoming of our study is that we did not quantitatively analyze preoperative glycemic control. However, Ramanujam et al did not find a statistically significant difference in preoperative hemoglobin A1C levels and healing time, despite high average preoperative hemoglobin A1C values in their patients (10). Conversely, a study by Marston found a direct correlation between hyperglycemia and wound healing.…”
Section: Discussionmentioning
confidence: 76%
“…This average is comparable to that of other studies of wound healing in diabetic populations. Recently, Ramanujam et al retrospectively reviewed 83 diabetic patients treated with STSGs for diabetic foot and ankle wounds and reported a median time to healing of 6.9 weeks among those patients without complications (10). Mahmoud et al prospectively studied patients with STSG versus conservative wound care for diabetic foot wounds and found a statistically significant reduction in mean hospital stay and healing time for those patients treated with STSG (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramanujam et al [8] retrospectively examined the success of STSG as a definitive treatment for wounds in patients with diabetes while Mahmoud et al [6] prospectively compared the effect on healing times of STSG versus conservative wound dressing in the treatment of diabetic foot ulcers. The remaining two studies evaluated the influence of meshing the STSG [7] and the use of 10% phenytoin ointment as a wound bed preparation [9] prior to STSG application.…”
Section: Resultsmentioning
confidence: 99%
“…There was no statistical difference between the two groups, and again all patients in the study healed completely. Ramanujam et al retrospectively analyzed STSG in 83 consecutive diabetic patients [8]. All of the patients healed successfully by the final follow-up, but this included repeat surgical procedures or additional graft applications.…”
Section: Resultsmentioning
confidence: 99%